Oligomeric lactate bio-based plasticizer as well as preparation method and application thereof
By preparing oligoslatinate bio-based plasticizers, the problems of poor low-temperature flowability and poor high-temperature thermal stability are solved, and the better thermal processing performance and toughness of PHA materials are achieved, and good biological performance is maintained.
Patent Information
- Application Number
- CN202411662485.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing bio-based plasticizers have poor fluidity at low temperatures and poor thermal stability at high temperatures, and have high raw materials costs and complex processes, resulting in insufficient market competitiveness.
Oligolactic acid ester is used as a bio-based plasticizer to prepare diethylene glycol monomethyl ether-oligolactic acid-cinnamic acid ester plasticizer through a two-step esterification reaction to improve its physical and chemical properties.
It improves the plasticizing properties of plasticizers, reduces the glass transition temperature and average melting temperature of PHA, enhances the thermal processing ability and toughness of the material, and has good biocompatibility and biodegradability.
Smart Images

Figure BDA0005143781560000011 
Figure FDA0005143781540000011 
Figure HDA0005143781570000011
Abstract
Description
Technical Field
[0001] The invention relates to a plasticizer and a preparation method and application thereof, and in particular to an oligolactic acid ester bio-based plasticizer and a preparation method and application thereof. Background Art
[0002] Polyhydroxyalkanoate (PHA) is a natural polyester obtained by microbial fermentation. It has become the hottest research object in the field of biomaterials due to its good biodegradability and biocompatibility. In addition, PHA also has unique material characteristics, such as nonlinear optical activity, piezoelectricity, odor barrier, etc. Among them, poly 3-hydroxybutyrate PHB is the most common form of PHA, and is one of the candidates to replace non-biodegradable plastics in high value-added fields such as food services, biomedicine and product packaging. However, at present, a large number of challenges are still restricting the development of PHB in commercial applications, such as the melting temperature of the polymer is close to the decomposition temperature, the processing range is narrow; high crystallinity, low toughness and impact strength; poor thermal stability, etc., and the realization of marketization still requires a lot of research. At present, traditional petroleum-based plasticizers have been banned in the fields of food, medical care, etc., and will affect the biodegradability of PHB to a certain extent, so this requires the development of bio-based environmentally friendly plasticizers with general performance.
[0003] Bio-based plasticizers are chemicals based on renewable resources, which are widely used in the production of plastics, rubber and other materials to improve the flexibility and processing properties of the materials. As an environmentally friendly alternative to traditional plasticizers, they have broad application prospects. However, in practical applications, they face problems such as insufficient physical and chemical properties, such as poor fluidity at low temperatures and poor thermal stability at high temperatures. On the other hand, the raw materials of bio-based plasticizers usually come from biomass resources such as vegetable oils, starch, and corn stalks. The cost is relatively high and the process is also complicated, resulting in insufficient market competitiveness of the final product. Therefore, continuous technological innovation and optimization of production processes are needed. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a bio-based oligomeric lactate plasticizer with excellent plasticizing properties; the second purpose of the present invention is to provide a method for preparing the above-mentioned bio-based oligomeric lactate plasticizer; the third purpose of the present invention is to provide the application of the above-mentioned bio-based oligomeric lactate plasticizer.
[0005] Technical solution: The oligomeric lactate bio-based plasticizer of the present invention has the following structural formula:
[0006]
[0007] Wherein, n is the number of lactic acid repeating units.
[0008] The preparation method of the above-mentioned oligomeric lactate bio-based plasticizer comprises the following steps:
[0009] (1) adding diethylene glycol monomethyl ether, lactic acid and a catalyst into a reactor and heating for reaction; after the reaction is completed, extracting a crude product, washing it to neutrality, and removing the solvent by rotary evaporation to obtain diethylene glycol monomethyl ether-oligomeric lactate;
[0010] (2) adding diethylene glycol monomethyl ether-oligomeric lactic acid ester, cinnamic acid and a catalyst into a reactor and heating for reaction; after the reaction is completed, extracting the crude product, washing it to neutrality, and then rotary evaporating to remove the solvent to obtain diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamic acid ester.
[0011] Wherein, in step (1), the catalyst is p-toluenesulfonic acid, and the mass of the catalyst is 0.4% to 0.6% of the total mass of the raw materials.
[0012] Wherein, in step (1), the molar ratio of diethylene glycol monomethyl ether to lactic acid is 1:2-3.
[0013] Wherein, in step (1), the temperature is heated to 120-160° C. and the reaction is carried out for 2-4 hours. Under such heating conditions, the activity of the catalyst is the best and the catalytic efficiency is the highest.
[0014] Wherein, in step (1), the vacuum degree of rotary evaporation is -0.1 MPa, and the distillation is carried out at 70-90° C. for 0.5-2 h. Under this rotary evaporation parameter, the solvent can be evaporated quickly.
[0015] Wherein, in step (2), the catalyst is a strongly acidic cation exchange resin, and the mass of the catalyst is 20-30% of the molar mass of cinnamic acid.
[0016] Wherein, in step (2), the molar ratio of diethylene glycol monomethyl ether-oligolactate to cinnamic acid is 1:2-3.
[0017] Wherein, in step (2), the temperature is heated to 160-200° C. and the reaction is carried out for 12-16 hours. Under such heating conditions, the activity of the catalyst is the best and the catalytic efficiency is the highest.
[0018] Wherein, in step (2), the vacuum degree of rotary distillation is -0.1 MPa, and the distillation is carried out at 70-90° C. for 0.5-2 h. Under this rotary distillation parameter, the solvent can be evaporated relatively quickly.
[0019] The oligomeric lactate bio-based plasticizer prepared by the above method is used in the preparation of polyhydroxyalkanoate PHA and poly 3-hydroxybutyrate PHB.
[0020] Principle of the invention: The present invention improves PHB by adding low molecular weight compounds. The addition of plasticizers can reduce the glass transition temperature (T g ) and the average melting temperature (Tm ), which is beneficial to the thermal processing of materials and reduces thermal degradation. At the same time, plasticizers are inserted between polymer segments, expanding the distance between polymers, improving processing properties, and making the material more tough and flexible.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: (1) The present invention uses lactic acid, diethylene glycol monomethyl ether and cinnamic acid as main raw materials, and chemically modifies lactic acid through a two-step esterification reaction. The diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamic ester plasticizer prepared by this method has low viscosity, light yellow transparent color, and good compatibility with PHA; compared with DOP and ATBC used in PHA, the plasticizer of the present invention has better plasticizing ability and can reduce the melting point T of PHA. m and glass transition temperature T g The effect of heat treatment makes the material easier to process. (2) The addition of the plasticizer of the present invention can increase the elongation at break of PHA and broaden the application scenarios. (3) The diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate plasticizers are all made of biomass raw materials, with good biocompatibility and biodegradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The infrared spectra of the raw materials and products of Example 1 are shown below:
[0023] Figure 2 This is a thermogravimetric test diagram of three plasticizer samples in Example 1;
[0024] Figure 3 Thermogravimetric test diagrams of three plasticized PHB samples and pure PHB for application implementation 1. DETAILED DESCRIPTION
[0025] The present invention is described in further detail below.
[0026] Example 1
[0027] (1) First step esterification reaction: lactic acid, diethylene glycol monomethyl ether and catalyst p-toluenesulfonic acid are added to a reactor and heated to react; the molar ratio of the raw material lactic acid to diethylene glycol monomethyl ether is 1:2, the mass of the catalyst is 0.5% of the total mass of the raw material, heated to 120°C, and reacted for 2 hours; after the reaction is completed, washed with deionized water to neutrality, and then vacuum distilled at -0.1 MPa and 70°C for 2 hours to remove residual water and ethyl acetate, to obtain diethylene glycol monomethyl ether-oligomeric lactate;
[0028] (2) Second step esterification reaction: add the diethylene glycol monomethyl ether-oligomeric lactic acid ester prepared in step (1), cinnamic acid and catalyst strong acid cation exchange resin into a reactor for heating reaction, wherein the molar ratio of diethylene glycol monomethyl ether-oligomeric lactic acid ester to cinnamic acid is 1:2, the mass of the catalyst is 20 parts of the molar mass of cinnamic acid, the model of the strong acid cation exchange resin is: 001X 7 (732), manufacturer: Fuchen Chemical; the heating reaction temperature is 160° C., and the reaction is carried out for 12 hours; after the reaction is completed, the crude reaction product is first extracted with ethyl acetate, washed with saturated sodium bicarbonate solution and deionized water until neutral, and then vacuum distilled at -0.1 MPa and 70° C. for 2 hours to remove residual water and ethyl acetate to obtain diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamic acid ester.
[0029] Example 2
[0030] (1) First step esterification reaction: lactic acid, diethylene glycol monomethyl ether and catalyst p-toluenesulfonic acid are added to a reactor and heated to react; the molar ratio of raw material lactic acid to diethylene glycol monomethyl ether is 1:2.5, the mass of the catalyst is 0.5% of the total mass of the raw material, heated to 130°C, and reacted for 3 hours; after the reaction is completed, washed with deionized water to neutrality, and then vacuum distilled at -0.1 MPa and 80°C for 2 hours to remove residual water and ethyl acetate, to obtain diethylene glycol monomethyl ether-oligomeric lactic acid ester;
[0031] (2) Second step esterification reaction: the diethylene glycol monomethyl ether-oligomeric lactic acid ester prepared in step (1), cinnamic acid and a catalyst strong acid cation exchange resin are added to a reactor and heated to react; the molar ratio of diethylene glycol monomethyl ether-oligomeric lactic acid ester to cinnamic acid is 1:2.5, the mass of the catalyst is 25 parts of the molar mass of cinnamic acid, the reaction is heated to 170° C. and reacted for 14 hours; after the reaction is completed, the crude reaction product is first extracted with ethyl acetate, washed with saturated sodium bicarbonate solution and deionized water until neutral, and then vacuum distilled at -0.1 MPa and 80° C. for 2 hours to remove residual water and ethyl acetate to obtain diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamic acid ester.
[0032] Example 3
[0033] (1) First step esterification reaction: lactic acid, diethylene glycol monomethyl ether and catalyst p-toluenesulfonic acid are added to a reactor and heated to react; the molar ratio of raw material lactic acid to diethylene glycol monomethyl ether is 1:3, the mass of the catalyst is 0.5% of the total mass of the raw material, heated to 140°C, and reacted for 3 hours; after the reaction is completed, washed with deionized water to neutrality, and then vacuum distilled at -0.1 MPa and 80°C for 2 hours to remove residual water and ethyl acetate, to obtain diethylene glycol monomethyl ether-oligomeric lactic acid ester;
[0034] (2) Second step esterification reaction: add the diethylene glycol monomethyl ether-oligomeric lactic acid ester prepared in step (1), cinnamic acid and catalyst strong acid cation exchange resin into a reactor and perform heating reaction; the molar ratio of diethylene glycol monomethyl ether-oligomeric lactic acid ester to cinnamic acid is 1:3, the mass of the catalyst is 30 parts of the molar mass of cinnamic acid, heat to 180°C, and react for 16 hours; after the reaction is completed, first extract the crude reaction product with ethyl acetate, wash it with saturated sodium bicarbonate solution and deionized water until neutral, and then vacuum distill at -0.1 MPa and 80°C for 2 hours to remove residual water and ethyl acetate to obtain diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamic acid ester.
[0035] Example 4
[0036] The first step of esterification reaction: lactic acid, diethylene glycol monomethyl ether and catalyst p-toluenesulfonic acid are added to a reactor for heating reaction; the molar ratio of raw material lactic acid and diethylene glycol monomethyl ether is 1:2, the mass of the catalyst is 0.5% of the total mass of the raw material, heated to 100°C, and reacted for 2 hours; after the reaction is completed, it is washed with deionized water to neutrality, and then vacuum distilled at -0.1MPa and 70°C for 2 hours to remove residual water and ethyl acetate to obtain diethylene glycol monomethyl ether-oligomeric lactic acid ester; the obtained diethylene glycol monomethyl ether-oligomeric lactic acid ester is tested for acid value, the acid value is high, which will affect the second step esterification reaction and the final product, so the second step reaction is no longer carried out.
[0037] The raw materials lactic acid, cinnamic acid, and product diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate in Example 1 were subjected to infrared spectrum testing. The test results are as follows: Figure 1 shown.
[0038] Figure 1 From the top to the bottom, 1, 2, 3 and 4 are lactic acid, cinnamic acid, diethylene glycol monomethyl ether and the product diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate. It can be seen from the infrared results that after the two-step esterification reaction, the product diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate CLDE is 3100-3010cm -1 -C=CH stretching vibration peaks appeared in the range of 1641 and 1575 cm -1 The stretching vibration of -C=C- skeleton on benzene ring and 769cm -1 Compared with lactic acid LA, CLPE is at 3421cm -1 No peak was detected at , indicating that there was no hydroxyl-containing substance in the product, and further indicating that the hydroxyl groups of lactic acid had been completely reacted. In summary, it can be considered that the final product, diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate, was successfully synthesized.
[0039] The thermogravimetric test was performed on the diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate CLDE and the comparative plasticizers ATBC and DOP in Example 1. The specific thermogravimetric results are as follows: Figure 2 As shown;
[0040] Figure 2 In the figure, curves 1, 2, and 3 are the thermogravimetric curves of plasticizers DOP, ATBC, and CLDE, respectively. It can be seen from the figure that compared with plasticizers DOP and ATBC, the initial decomposition temperature T i The highest temperature is about 247.5°C, indicating that the diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate CLDE prepared by the product of the present invention has excellent thermal stability. The thermal stability of the plasticizer is related to its molecular structure and molecular weight. The CLDE prepared by the product of the present invention is a small molecule oligomer, and its molecular weight is much higher than that of the comparative plasticizers DOP and ATBC, so it can show excellent thermal stability during the programmed temperature rise process.
[0041] Application Example 1
[0042] 3 g of PHB and 0.45 g of diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate prepared in Example 1 were dissolved in 100 mL, refluxed for 1 hour, cooled and cast into a glass dish, and dried for 2 days after chloroform evaporated to obtain a sample. The obtained PHB sample was subjected to thermogravimetric test and tensile test.
[0043] Comparative Example 1
[0044] The DOP plasticizer in the prior art was used in the same steps as in Application Example 1 to prepare PHB comparative sample 1.
[0045] Comparative Example 2
[0046] The ATBC plasticizer in the prior art was prepared using the same steps as in Application Example 1 to obtain PHB comparative sample 2.
[0047] The PHB sample prepared by the product of the present invention in Application Example 1 and the two PHB comparative samples obtained were subjected to thermogravimetric testing. The specific thermogravimetric results are as follows: Figure 3 As shown in the figure, curves 1, 2, 3 and 4 are the thermal weight loss curves of ATBC plasticization, DOP plasticization, pure PHB and diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate CLDE plasticization. It can be seen from the figure that after adding 10 parts (0.45g) of plasticizer DOP and ATBC to PHB, the initial decomposition temperature T iOn the contrary, it has decreased, which may be due to the poor stability of the plasticizer itself, causing the plasticized PHB sample to decompose at a relatively low temperature. The diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamate CLDE prepared by the product of the present invention has good thermal stability itself, which can play a certain effect in delaying the thermal degradation of PHB, and can increase the decomposition temperature of the plasticized PHB material to a certain extent, and expand the processing temperature space of the plasticized material.
Claims
1. A bio-based oligolactic acid plasticizer, characterized in that: Its structural formula is as follows: Wherein, n is the number of lactic acid repeating units.
2. A method for preparing the oligolactic acid ester bio-based plasticizer according to claim 1, characterized in that: The following steps are involved: (1) adding diethylene glycol monomethyl ether, lactic acid and a catalyst into a reactor and heating for reaction; after the reaction is completed, extracting a crude product, washing it to neutrality, and removing the solvent by rotary evaporation to obtain diethylene glycol monomethyl ether-oligomeric lactate; (2) adding diethylene glycol monomethyl ether-oligomeric lactic acid ester, cinnamic acid and a catalyst into a reactor and heating for reaction; after the reaction is completed, extracting the crude product, washing it to neutrality, and then rotary evaporating to remove the solvent to obtain diethylene glycol monomethyl ether-oligomeric lactic acid-cinnamic acid ester.
3. The method for preparing the oligomeric lactate bio-based plasticizer according to claim 2, characterized in that: In step (1), the catalyst is p-toluenesulfonic acid, and the mass of the catalyst is 0.4% to 0.6% of the total mass of the raw materials.
4. The method for preparing the oligomeric lactate bio-based plasticizer according to claim 2, characterized in that: In step (1), the molar ratio of diethylene glycol monomethyl ether to lactic acid is 1:2-3.
5. The method for preparing the oligomeric lactate bio-based plasticizer according to claim 2, characterized in that: In step (2), the catalyst is a strongly acidic cation exchange resin, and the mass of the catalyst is 20-30% of the molar mass of cinnamic acid.
6. The method for preparing the oligomeric lactate bio-based plasticizer according to claim 2, characterized in that: In step (2), the molar ratio of diethylene glycol monomethyl ether-oligolactate to cinnamic acid is 1:2-3.
7. The method for preparing the oligomeric lactate bio-based plasticizer according to claim 2, characterized in that: In step (1), the temperature is heated to 120-160° C. and the reaction is carried out for 2-4 hours.
8. The method for preparing the oligomeric lactate bio-based plasticizer according to claim 2, characterized in that: In step (2), the temperature is heated to 160-200° C. and the reaction is carried out for 12-16 hours.
9. The method for preparing the oligomeric lactate bio-based plasticizer according to claim 2, characterized in that: The vacuum degree of the rotary evaporation in step (1) is -0.1 MPa, and the distillation is carried out at 70-90° C. for 0.5-2 h; the vacuum degree of the rotary evaporation in step (2) is -0.1 MPa, and the distillation is carried out at 70-90° C. for 0.5-2 h.
10. Use of the oligolactic acid ester bio-based plasticizer according to claim 1 in the preparation of polyhydroxyalkanoate (PHA) and poly 3-hydroxybutyrate (PHB).
Citation Information
Patent Citations
Polyhydroxyl carboxylic acid modified material capable of completely biodegrading
CN101148536A
Plasticizing method available to low-temperature forming of polylactic acid
CN110079064A
Preparation method and application of lactic acid-based environment-friendly plasticizer
CN112920394A
Polylactic acid plasticizer and preparation method thereof
CN112940235A
Preparation method of cyclohexyl-terminated glutaric acid oligomeric lactate plasticizer for PLA (polylactic acid) and PVC (polyvinyl chloride)
CN114956998A
Cited By
Terpene alcohol ester full-bio-based polylactic acid plasticizer and application thereof
CN120794846A